Pharmacological activities and gas chromatography–mass spectrometry analysis for the identification of bioactive compounds from Justicia adhatoda L. - Musa, Muhammad; Jan, Gul; Jan, Farzana Gul; Hamayun, Muhammad; Irfan, Muhammad; Rauf, Abdur; Alsahammari, Abdulrahman; Alharbi, Metab; Suleria, Hafiz A. R.; Ali, Niaz (Frontiers in Pharmacology, 2022)
The current study aimed to assess the pharmacological potential of Justicia adhatoda by evaluating the presence of biologically active compounds using Gas chromatography–mass spectrometry approach and to undertake biological activities for the effectiveness of the present compounds using standard tests. A total of 21 compounds were identified in the Gas chromatography–mass spectrometry analysis of the ethyl-acetate fraction where, 14 of the identified compounds are recognized for their pharmacological potential in literature. Total 4 fractions (ethyl-acetate, chloroform, n-hexane, and aqueous) were evaluated for pharmacological activities. In carrageen induced inflammation, chloroform fraction exhibited high anti-inflamatory activity (46.51%). Similarly, the analgesic potential of ethyl acetate fraction was most effective (300 mg/kg) in acetic acid induced test. Similarly, in formalin test ethyl acetate fraction exhibited maximum inhibition in both early (74.35%) and late phases (88.38). Maximum inhibition of pyrexia (77.98%) was recorded for ethyl acetate fraction (300mg/kg). In DPPH assay, ethyl acetate fraction revealed highest scavenging potential compared to other fractions (50µg/mL resulted in 50.40%, 100µg/mL resulted in 66.74% scavenging).